IMPLEMENTATION OF INFRASTRUCTURE DEVELOPMENT POLICY IN COMMUNITY ECONOMIC DEVELOPMENT IN MERANTI ISLANDS DISTRICT - Deni Muhammad Wahyu; Mustiqowati Ummul F (Indonesian Journal of Social Sciences, Policy and Politics, 2023)
This study aims to determine the implementation of development and the impact on development carried out by the government of the Meranti Islands Regency. This research is descriptive with a qualitative explanation. Data collection techniques were obtained through interviews, observation, and documentation. Data collection techniques included data reduction, data presentation, and conclusion. There were eight key informants, namely the Head of the Development Planning Agency at Sub-National, two general administration subdivisions, and five people from the Meranti Islands Regency. The results of this study indicate that the implementation and impact of the development carried out in Meranti Islands Regency have not optimally provided welfare to the people of Meranti Islands Regency. It is necessary to carry out various efforts, from prevention to supervision, in every development process carried out in the Meranti Islands Regency.